Utilizing Organic Aromatic Melamine Moiety to Modify Poly(Vinyl Chloride) Chemical Structure and Micro CuO That Plays an Important Role to Enhance Its Photophysical Features - Mohammed Hussein Al-Mashhadani; Ekhlas Abdulkhadiar Salman; Amani Ayad Husain; Mustafa Abdallh; Muna Bufaroosha; Emad Yousif (Universitas Gadjah Mada, 2022)
Three arms Schiff base unit based on melamine moiety was synthesized and introduced to polyvinyl chloride (PVC) to produce a modified PVC polymer. The polymer composite of new modified PVC polymer was blended with micro copper oxide as a reflecting mirror of UV light to enhance the photostability of PVC. Three different concentrations of micro copper oxide (0.01–0.03 wt.%) were mixed with the modified PVC and cast as a thin film. The photostability test has shown high resistance to photodegradation upon exposure to UV light. In this work, different approaches were applied to examining doped modified PVC's thin film efficiency against photodegradation after exposure to UV light for 300 h in an ambient atmosphere. The exhibited studies, such as infrared spectroscopy and weight loss percentage, have demonstrated the improvement of photophysical properties for modified PVC and blended modified films in comparison to blank PVC polymeric films. These outcomes are so interesting as they could contribute to reducing the consumption of PVC around the world hence its waste causing huge environmental problems for the marine ecosystem.